2017
DOI: 10.5194/amt-10-2969-2017
|View full text |Cite
|
Sign up to set email alerts
|

Mixing layer height as an indicator for urban air quality?

Abstract: Abstract. The mixing layer height (MLH) is a measure for the vertical turbulent exchange within the boundary layer, which is one of the controlling factors for the dilution of pollutants emitted near the ground. Based on continuous MLH measurements with a Vaisala CL51 ceilometer and measurements from an air quality network, the relationship between MLH and near-surface pollutant concentrations has been investigated. In this context the uncertainty of the MLH retrievals and the representativeness of ground-base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 82 publications
5
102
0
Order By: Relevance
“…The PBL heights retrieved by measuring the attenuated backscatter profile of MPL and CL31 still exist some uncertainties (Tang et al, 2016;Geiß et al, 2017). Tang et al (2016) found that PBL height cannot be correctly obtained through sudden changes in the attenuated backscatter profiles.…”
Section: Relationship Between Pm 25 Mass Concentration and Pbl Heightmentioning
confidence: 99%
“…The PBL heights retrieved by measuring the attenuated backscatter profile of MPL and CL31 still exist some uncertainties (Tang et al, 2016;Geiß et al, 2017). Tang et al (2016) found that PBL height cannot be correctly obtained through sudden changes in the attenuated backscatter profiles.…”
Section: Relationship Between Pm 25 Mass Concentration and Pbl Heightmentioning
confidence: 99%
“…All MLH data presented follow this method (for more detail see Schäfer et al, 2015) unless otherwise noted. The influence of different options of the proprietary software and an comparison with the more sophisticated approach COBOLT (COntinuous BOundary Layer Tracing) on the retrieved MLH is discussed in detail by Geiß et al (2017). It was found that the proprietary software slightly tends to overestimate the MLH compared to COBOLT.…”
Section: Ceilometermentioning
confidence: 99%
“…Complementing the BLUME measurements (see Stülpnagel et al, 2015, or Geiß et al, 2017, for details) were additional PM 10 filter samples collected for elemental carbon (EC) and organic carbon (OC), ions, and organic tracer analysis; intermittent canister and cartridge samples for the quantification of NMVOCs from an inlet next to the PM 10 inlet on the roof of the measurement station; a quadrupole proton transfer reaction mass spectrometer (high-sensitivity PTR-MS; Ionicon) up in the van for the measurement of NMVOCs; a set of particle instruments to measure number concentration, size distribution, and surface area also located in the van (Sect. 2.2.4); and a ceilometer CL51 (Vaisala GmbH, Hamburg) situated on the roof of the kindergarten.…”
Section: Instrument Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations